The effect of the physical environment and levels of activity on affective states - Kinnafick, F.; Thøgersen-Ntoumani, Cecilie (Academic Press, 2014)
The physical environment and physical activity can independently improve positive affect. The current studies investigated the effects of two opposing environments (urban versus natural) and levels of activity (walking and sitting) on affective states in either a laboratory (study 1) or an outdoor setting (study 2). While doing each activity (walking and sitting in each environment), participants watched film clips of urban or natural outdoor settings (study 1), or were naturally immersed in an urban or a natural environment (study 2). Measures of affect were administered pre, mid and post each condition. Findings highlighted the benefits of being immersed in a natural outdoor environment with physical activity being key for positive effects on energy. Short bouts of sedentary behaviour increased state negative affect, tiredness, and decreased energy levels. Attempts by policy-makers, urban planners and public health promoters should encourage greater use of natural open space to promote acute psychological well-being.